Vicarious Ostracism and its Potential Interaction with Minimal Group Membership - Spoerle, Alexa; Claypool, Heather (Journal of Student Research, 2024)
Vicarious ostracism occurs when individuals experience other people’s ostracism as though it were their own. In this experiment, we attempted to replicate the vicarious ostracism effect, and we also tested whether it was moderated by the group membership of the ostracized target. Participants were placed in a minimal group and watched a person (“Player 2”) play a virtual ball-tossing game. “Player 2” was labeled as either a minimal ingroup or outgroup member and was either included or ostracized by co-players in the game. Participants’ own fundamental needs and mood were measured following the game. Results showed that those watching an ostracism game reported lower fundamental needs and worse mood than did those watching an inclusion game (a vicarious ostracism effect), but the group membership of the target person did not moderate these effects. Future research is needed to better understand when and whether the group membership of the witnessed ostracized target impacts personal feelings of ostracism.